Lymphocytic interstitial pneumonia in a patient with mixed connective tissue disease – A case report. (2018) - Kuo, Chin-Wei; Chang, Kung-Chao; Chang, Han-Yu; Huang, Tang-Hsiu
Abstract: Lymphocytic interstitial pneumonia (LIP) is an uncommon interstitial lung disease that is characterized by an interstitial infiltrate of lymphoplasmacytic cells. While idiopathic LIP appears to be extremely rare, most reported cases of LIP have been associated with coexisting immune derangements, particularly autoimmune diseases such as Sjögren's syndrome. In this report, we describe the presentation of LIP in a patient with underlying mixed connective tissue disease.